2021
DOI: 10.3390/antiox10050780
|View full text |Cite
|
Sign up to set email alerts
|

Plant Feed Additives as Natural Alternatives to the Use of Synthetic Antioxidant Vitamins in Livestock Animal Products Yield, Quality, and Oxidative Status: A Review

Abstract: The interest for safe and natural foods of animal origin is currently increasing the use of plant feed additives (PFA) as antioxidants in animal nutrition. However, studies with livestock animals dealing with PFA as antioxidants are scarce. The aim of the present review was to evaluate the antioxidant impact of PFA compared with synthetic vitamins on animal food product yield and quality. For this purpose, peer-reviewed studies published between 2000 and 2020 were collected. Most papers were carried out on rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…The dynamic balance between oxidation and antioxidant activity in the circulatory system plays a critical role in the health and productive performance of livestock ( 47 ). The rich functional compounds in nature-derived feedstuffs make them an attractive component to improve the antioxidant status of animals, thereby improving the quality of products ( 47 49 ). Currently, consumers are interested in safe and natural foods of animal origin and in some cases, they are also willing to pay a premium price for them ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic balance between oxidation and antioxidant activity in the circulatory system plays a critical role in the health and productive performance of livestock ( 47 ). The rich functional compounds in nature-derived feedstuffs make them an attractive component to improve the antioxidant status of animals, thereby improving the quality of products ( 47 49 ). Currently, consumers are interested in safe and natural foods of animal origin and in some cases, they are also willing to pay a premium price for them ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rich functional compounds in nature-derived feedstuffs make them an attractive component to improve the antioxidant status of animals, thereby improving the quality of products ( 47 49 ). Currently, consumers are interested in safe and natural foods of animal origin and in some cases, they are also willing to pay a premium price for them ( 49 ). TAC reflects the cumulative effects of enzymatic and non-enzymatic antioxidants present in plasma and body fluids ( 47 , 48 ), whereas MDA is generated because of lipid peroxidation that could be measured as a biomarker of oxidative stress ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In swine, PFA has been mostly tested as alternatives to antimicrobials rather than as antioxidants, particularly after the ban of in-feed antibiotic use in 2006 [ 18 , 19 , 20 ], whereas in ruminants, PFA (usually essential oils) have been widely investigated as rumen modifiers [ 21 , 22 ]. Nevertheless, some trials comparing natural to synthetic antioxidants have also been conducted, in swine, rabbits, and ruminants, in order to assess their capacity in ameliorating products yield and quality [ 23 ]. However, only a few studies have been conducted in livestock to evaluate the antioxidant role of PFAs in comparison to synthetic molecules in affecting their performances.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of natural extracts on product quality, oxidative stability, and shelf life in ruminants, swine, and rabbits have been reviewed. The authors reported that the effects of plant additives are different but similar to synthetic vitamin E, thus suggesting their role as possible natural substitutes [ 11 ]. The impact of plant additives in poultry nutrition has also been analyzed, based on the selection of literature published in the last 20 years [ 12 , 13 ].…”
mentioning
confidence: 99%